Estuarine and Coastal Ecosystems as Defense Against Flood Damages: An Economic Perspective - Barbier, Edward B. (Frontiers in Climate, 2020)
The rapid loss of estuarine and coastal ecosystems (ECEs) in recent years has raised concerns over their role in protecting coastal communities from storms that damage property, cause deaths, and inflict injuries. This paper reviews valuation studies of the protective service of ECEs in terms of reducing flood damages. Although the number of studies have grown significantly, there is still a need for a greater range of studies in more locations and for a wider variety of ecosystems. This review also examines, from an economic perspective, the issues and challenges surrounding estimating the protective benefits of ECEs, as exemplified by some of the recent valuation studies. Recent developments in valuation methods are summarized and critically reviewed. Important challenges remain in valuing coastal ecosystems as a defense against flood damages. The review discusses two of them, such as how protective benefits are subject to spatial variability and dependent on connectivity across “seascapes.” These challenges, along with analyzing the multiple benefits of estuarine and coastal ecosystems, are important areas of future research priority.